2012
DOI: 10.1111/j.1600-0633.2012.00552.x
|View full text |Cite
|
Sign up to set email alerts
|

Summer habitat use and feeding of juvenile Arctic charr, Salvelinus alpinus, in the Canadian High Arctic

Abstract: –  Owing to limited knowledge of the habitat use and diet of juvenile Arctic charr from the High Arctic, particularly young‐of‐the‐year (YOY), we assembled data obtained from samples taken in and around Lake Hazen, Nunavut, Canada, to assess juvenile habitat use and feeding. Juvenile charr demonstrated a preference for stream environments, particularly those fed by warm upstream ponds. Charr occupying both stream and nearshore lake habitats were found to feed similarly, with chironomids occurring most frequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 68 publications
(129 reference statements)
0
31
0
Order By: Relevance
“…The present study exemplifies how the differences in the use of surface prey (terrestrial prey and emerged aquatic insects) among sympatric species can constitute an important adaptive feature to reduce interspecific competition in riverine fish communities during the summer. Thus, our findings suggest that Studies describing the trophic ecology of Arctic charr in running waters are scarce (but see Moore & Moore, 1974;Stenzel, 1987;Sinnatamby et al, 2012;Sánchez-Hernández et al, 2016). Moore & Moore (1974) observed that small Arctic charr (\100 mm) fed mostly on Chironomidae larvae.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…The present study exemplifies how the differences in the use of surface prey (terrestrial prey and emerged aquatic insects) among sympatric species can constitute an important adaptive feature to reduce interspecific competition in riverine fish communities during the summer. Thus, our findings suggest that Studies describing the trophic ecology of Arctic charr in running waters are scarce (but see Moore & Moore, 1974;Stenzel, 1987;Sinnatamby et al, 2012;Sánchez-Hernández et al, 2016). Moore & Moore (1974) observed that small Arctic charr (\100 mm) fed mostly on Chironomidae larvae.…”
Section: Discussionmentioning
confidence: 74%
“…Likewise, Stenzel (1987) found that the diet of juvenile Arctic charr is mainly composed of chironomids and other dipteran larvae. Recently, Sinnatamby et al (2012) confirmed Data are displayed for each month. The overlap/similarity is considered high when the index value exceeds 60% (values in bold)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several char studies have been conducted in northern Ellesmere Island in Quttinirpaaq National Park and at Alert (a military, meteorological and scientific research station) where there are many charcontaining lake and river systems, Lake Hazen being the most wellknown (Babaluk et al, 1997;Babaluk et al, 2007a;Babaluk et al, 2007b;Babaluk et al, 2009;Gantner et al, 2010b;Guiguer et al, 2002;Sinnatamby et al, 2012). Most char are landlocked, although Heintzelman Lake (13.5 km 2 ; maximum depth 15 m), with a close connection to the sea, has anadromous and resident char van der Velden et al, 2012).…”
Section: Nunavut: East and North Arcticmentioning
confidence: 97%
“…Few studies have addressed the feeding behaviour of stream‐dwelling S . alpinus , but the available studies highlight that juveniles predominantly feed on Chironomidae larvae and other aquatic dipterans during summer (Moore & Moore, ; Stenzel, ; Sinnatamby et al , ). This study addresses seasonal shifts in the feeding behaviour of YOY S .…”
Section: Diet Composition (%) Of Yoy Salvelinus Alpinus Data Are Dismentioning
confidence: 99%